The Effect of Limb Length Discrepancy and Anteversion on The Post-Operational Efficacy of Total Hip Arthroplasty - Tiwari, Shashi Ranjan; Singh, Saroj; Gupta, Radheshyam; Cheng, Liming (British Journal of Healthcare and Medical Research, 2023)
Total hip replacement (THA) is a common reason for patient discontent and lawsuits against doctors. An effective technique should be used by surgeons conducting THA to reduce both anteversion and limb length discrepancy (LLD). Therefore, there is a current need for a repeatable method that effectively reduces postoperative LLD and anteversion without lengthening the surgical procedure and simple to use. While numerous preoperative and intraoperative techniques are detailed in the literature, none of them are without drawbacks. Following total hip replacement, we are providing an extensive review of literatures on limb length discrepancy and anteversion along with their effects, and various methods to prevent them. By combining preoperative and intraoperative methods, we propose that every effort should be made to reduce postoperative limb length discrepancy as well as anteversion.